A new species of Cnemidophorus of the lacertoides species group from the eastern sierras de Córdoba, Central Argentina (Lacertilia, Teiidae) - Cei, José Miguel Alfredo María (1991)
A new taxonomic status may be supported by significant morphological characters for the populations of the Cnemidophorus lacertoides species group scattered on the eastern embossments of the Sierras de Córdoba, from Tolumba to the Punilia department. The northermost Argentine populations of Cnemidophorus lacertoides Duméril & Bibrón 1839 may be indicated for the Achiras hills west of Rio Cuarto northwards. Beyond the Sierra of Tolumba a dry, Chacoan area, widely colonized by Cnemidophorus ocellifer, appears as an extensive ecological barrier separating our Cnemidophorus sp. nov. from the northernmost populations of Cnemidophorus lacertoides reported by Peracca as C. leachei (1897).